Characterization and simulation of structural fabrics – Part 2: Evaluating process simulation software in a product development cycle. Issue 6 (November 2015) - O'Sullivan, Liam
Abstract : Part 1 of this article, published in the March/April 2015 issue of Reinforced Plastics, presented an insight into multiaxial reinforcements specialist FORMAX's approach to materials characterization, simulation of processing and composites performance. In this concluding article, Liam O'Sullivan, KTP Associate and Composite Engineer at FORMAX, presents a case study of a typical automotive part and examines the benefits of this approach, including the development of optimized fabric architecture. This process involves the use of FORMAX's recently developed capabilities to measure drape and permeability characteristics of reinforcement fabrics, which have been developed as part of a two-year Knowledge Transfer Partnership (KTP) with the University of Nottingham and Innovate UK.